The Effect of Pruning and Growing Media Composition on Arbuscular Mycorrhizal Propagation - Happy Widiastuti; Salsa Bilah A; A Topani (Journal of Tropical Mycorrhiza, 2023)
The symbiosis of arbuscular mycorrhizal fungi with plants is the oldest symbiosis in the world. The obligate nature of mycorrhizal fungi in symbiotic relationships is believed to underlie its enduring presence to this day. The application of arbuscular mycorrhizal fungi (AMF) based fertilizers has become increasingly common. Spores are the most important organs that determine the quality of AMF-based fertilizers, along with AMF colonization in the roots. The production of AMF spores is greatly influenced by plant physiology, including photosynthesis processes affected by canopy abundance, as well as the type of planting medium, which determines plant root growth and AMF habitat. This study was conducted to investigate the effect of pruning and planting medium composition on AMF infection and spore production in AMF propagation using sorghum as the host plant. The pruning levels tested were at one, two, and three months after germination, and thereafter, each plant was maintained for 136 days after planting (DAP). The tested planting medium composition was the ratio between zeolite and compost in five different compositions: (v/v) 1) 100:0, 2) 90:10, 3) 70:30, and 4) 50:50. The chemical characteristic of compost used was contained 15.5% C, 1.49% N, 2.54% P2O5, 1.49% K2O, pH 6.6, and some microelements such as Cr, Fe, Zn, and Mn at 5.2 ppm, 5961 ppm, 294 ppm, and 199 ppm, respectively. The Sukabumi‘s zeolite used had a size of 2-3 mm. Propagation of AM fungal spores was carried out using polybags containing 10 kg of medium according to the treatment. Plant maintenance was carried out by alternating between watering with water and Johnson nutrient solution. Watering was performed until the plants were 120 days old, and subsequently, no watering was done until 136 days after planting. The observed parameters were the development of AMF spore numbers until a 4.5-month incubation period. The results showed that pruning time can affect spore production if the plant has reached a certain vegetative age, which is three months for sorghum. Additionally, adding 10% compost to zeolite medium can enhance spore formation, even though sorghum growth may not be at its maximum in this medium composition.